MALDI-TOF mass spectrometry identification of yeast-form fungi: A comparison between methods - Araújo, Max Roberto Batista; Seabra, Luisa Ferreira; Bernardes Sousa, Mireille Ângela (Clinical and Biomedical Research, 2019)
Introduction: Identification of yeast species has clinical and epidemiological value. Different methods can be used, such as chromogenic media, microculture on corn meal agar with Tween 80, as well as conventional biochemical and automated methods. Recently, proteomic studies employing matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry have been a major advance in diagnosis due to speed of execution and accuracy of results. Methods: For this study, 79 yeast samples were submitted to identification using chromogenic medium, microculture on corn meal-Tween 80 agar, VITEK® 2 Compact identification, and MALDI-TOF mass spectrometry. Results: Most of the 79 samples were identified, with differences in the performance of the methods used. Colonial morphology and microscopy were compatible with the genus Candida. MALDI-TOF mass spectrometry had the best performance, with 78 strains identified (98.7%), compared to VITEK® 2 Compact (92.4%) and microculture on corn meal agar (70.9%). Conclusion: MALDI-TOF mass spectrometry using the VITEK® MS instrument performed best and has proven to be a revolutionary method in clinical microbiology laboratories. Regarding the identification of C. albicans and C. tropicalis, the chromogenic medium had excellent performance, thus being a good option to optimize the process. Keywords: Mass spectrometry; matrix-assisted laser desorption-ionization; candidiasis; Candida; yeasts